Multinucleon Transfer in 40Ar (15 MeV/nucleon) + 64Ni via High-Resolution Studies of Momentum Distributions - Gkatzogias, Konstantinos; Souliotis, Georgios; Koulouris, Stergios; Giannitsa, Chryssi; Fasoula, Olga; Veselsky, Martin; Yennello, Sherry; Bonasera, Aldo (HNPS Advances in Nuclear Physics, 2024)
Multinucleon transfer (MNT) reactions have been extensively used in recent years as an effective tool to move further toward the neutron-rich side of the chart of nuclides. The efficient productionof these exotic nuclides is currently at the epicenter of the research interest in facilities around the world. The current contribution focuses on our efforts to systematically study the reaction mechanism of the reaction of a 40Ar beam at 15 MeV/nucleon with a 64Ni target through a detailed analysis of momentum distributions of various reaction channels. The experimental data presented in this work were obtained with the MARS spectrometer at the Cyclotron Institute of Texas A&M University. The experimental distributions are compared with two dynamical models, the Deep-Inelastic Transfer (DIT) model and the Constrained Molecular Dynamics (CoMD) model, followed by the de-excitation code GEMINI. In this contribution we study mass and momentum distributions for various reaction channels that result in neutron rich products. The comparison of the data with our calculations indicates agreement of the model calculation with the data in the dissipative part of the p/A spectra. The quasielastic part cannot be described by the models hinting to reaction mechanisms beyond successive nucleon exchange.